2016
DOI: 10.1016/j.vph.2015.10.010
|View full text |Cite
|
Sign up to set email alerts
|

The vasorelaxant effect of gallic acid involves endothelium-dependent and -independent mechanisms

Abstract: The mechanisms of action involved in the vasorelaxant effect of gallic acid (GA) were examined in the isolated rat thoracic aorta. GA exerted a relaxant effect in the highest concentrations (0.4-10mM) in both endothelium-intact and endothelium-denuded aortic rings. Pre-incubation with L-NAME, ODQ, calmidazolium, TEA, 4-aminopyridine, and barium chloride significantly reduced the pEC50 values. Moreover, this effect was not modified by indomethacin, wortmannin, PP2, glibenclamide, or paxillin. Pre-incubation of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
17
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(18 citation statements)
references
References 20 publications
1
17
0
Order By: Relevance
“…Quercetin also improved NOS3 expression in the mesenteric vessels (114%, Figure 6), although a significant difference was not observed (p = .062), demonstrating that small resistance vessels (mesenteric vascular bed), as well as conductance arteries (aorta), can also be appropriate tissues to access the effects of quercetin on NOS expression/activities (Duarte et al, 2002;Shen et al, 2012). Oliveira et al, 2016;Shen et al, 2012). These actions also contribute to the total vasoactive effects of these polyphenolic compounds as part of their endothelium-dependent mechanisms.…”
Section: Resultsmentioning
confidence: 95%
“…Quercetin also improved NOS3 expression in the mesenteric vessels (114%, Figure 6), although a significant difference was not observed (p = .062), demonstrating that small resistance vessels (mesenteric vascular bed), as well as conductance arteries (aorta), can also be appropriate tissues to access the effects of quercetin on NOS expression/activities (Duarte et al, 2002;Shen et al, 2012). Oliveira et al, 2016;Shen et al, 2012). These actions also contribute to the total vasoactive effects of these polyphenolic compounds as part of their endothelium-dependent mechanisms.…”
Section: Resultsmentioning
confidence: 95%
“…Thus, an inhibition of renin is suggested to suppress the production of angiotensin II, which in turn results in reduction of blood pressure. Few in vitro studies have further demonstrated the vasorelaxation effect by gallic acid 14,15 which was mediated through nitric oxide/cGMP signaling pathway. Gallic acid may act as a potassium channel opener and also as a calcium channel blocker to cause vasorelaxation.…”
Section: Resultsmentioning
confidence: 99%
“…Gallic acid may act as a potassium channel opener and also as a calcium channel blocker to cause vasorelaxation. 15 The resultant vasorelaxation effect may reduce the total peripheral resistance resulting in reduction of blood pressure. Interestingly, our recent study has shown that the aqueous and methanolic extract of S. polyanthum leaves extract have some vasorelaxation properties when tested on isolated thoracic aorta rings of WKY and SHR rats.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Inhibitions of Ca 2+ influx through voltage-dependent calcium channels (VDCC) by the most active fraction of V. pubescens were assessed as described by Oliveira et al. [ 22 ]. Denuded aortic rings were equilibrated for 30 min in normal KPS.…”
Section: Methodsmentioning
confidence: 99%